International Olympic Committee consensus statement on the health and fitness of young people through physical activity and sport - Mountjoy, M.; Andersen, L. B.; Armstrong, N.; Biddle, S.; Boreham, C.; Brandl Bedenbeck, H. P.; Ekelund, U.; Engebretsen, L.; Hardman, K.; Hills, A.; Kahlmeier, S.; Kriemler, S.; et al. (British Journal of Sports Medicine, 2011)
The International Olympic Committee (IOC) recognises the health and fitness benefits of physical activity (PA) and sport as stated in recommendation #51 from the Olympic Movement in Society Congress held in Copenhagen, 2009: "Everyone involved in the Olympic Movement must become more aware of the fundamental importance of Physical Activity and sport for a healthy lifestyle, not least in the growing battle against obesity, and must reach out to parents and schools as part of a strategy to counter the rising inactivity of young people.